Penggunaan PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS DIGITAL ARTIFICIAL INTELIGENCE (AI) CHAT GPT DALAM PENINGKATAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS 5 SD NEGERI TEGALPAPAK 01 KECAMATAN PAGELARAN - Wawan Kurniawan; Mustasyfiah Kamilah; Yanti Ardilasari; Putri Widia Andriani; Rt Upi Supenti; Anesa Utami; Herlina (Cakrawala Pedagogik, 2026)
This study aims to analyze the use of Artificial Intelligence (AI)-based learning media, specifically Chat GPT, in improving English learning outcomes for fifth-grade students at SD Negeri Tegalpapak 1. AI technology in education plays an important role in the digital era because it can create a more interactive, personalized, and engaging learning process for students. This research employs a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results show that the use of Chat GPT as a learning medium has a positive impact on student’s learning motivation, activeness, and self-confidence in communicating in English. Students feel more enthusiastic and independent in learning because Chat GPT helps them understand the material in an enjoyable and easily accessible way. From the teacher’s perspective, Chat GPT provides variation in teaching methods and helps create a more dynamic classroom atmosphere. However, challenges such as internet connectivity and mastery of Chat GPT instructions remain obstacles in its implementation. Overall, this study concludes that Chat GPT can be an effective learning medium that enhances English learning outcomes for elementary school students and should be considered as an innovative approach in digital-era education.